Kasus Penistaan Agama dalam Tabloid Monitor Tahun 1990 - 1991 - Zharfan, Fariha Alghina (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to find out and understand the history of blasphemy in the mass media in Indonesia, especially regarding the case of blasphemy in the Monitor Tabloid starting from its background, public response to the case, to its resolution. The research method used is the historical research method. The historical research method is a research method consisting of four stages: heuristics, verification, interpretation, and historiography. Based on the results of the research conducted, it can be known and understood that: the publication of the article